A trajectory of belonging: negotiating conflict and identity in an early childhood centre - Strycharz-Banaś, A; Dalli, C; Meyerhoff, M (Taylor & Francis, 2020)
Using the concept of a trajectory, we trace one child’s negotiation of his sense of belonging within his early childhood centre through analysing his participation in conflict and conflict-like interactions. Video data were gathered 2 days a week over a 6-month period from the start of his attendance at the centre. Sociolinguistic interactional analysis showed the child’s experience was one of learning and testing the norms and rules of centre life allowing him to negotiate a sense of belonging that straddled the identities of being a helper and eventually a member of the ‘big boys’ group.